Climate change and Africa : the normative framework of the African Union - Pallangyo, Daniel Mirisho (North-West University, 2013)
There is enough evidence on how climate change consequences will adversely affect Africa despite the fact that it is the continent that has least contributed to the problem. The international climate change regime recognises Africa's vulnerability to climate change and provides for special treatment under the United Nations Framework Convention on Climate Change (the UNFCCC). Thus, the international climate change regime presents an opportunity for African countries to adapt and mitigate the consequences of climate change through the UNFCCC mechanism. However, the international climate change legal regime has not been able to adequately assist African countries to address the consequences of climate change under the vulnerability principle. Although the current international climate change regime requires developed countries to reduce their greenhouse gas (GHG) emissions, Africa needs to take steps itself to address the problem, because it is most vulnerable to the consequences of climate change. The African Union (AU) could play a great role in ensuring that the international climate change regime addresses the consequences of climate change in the region. This could be done through fostering strong African common positions during international climate change negotiations. A strong common position could strengthen African bargaining power and might result in more funding, capacity building and technology development and transfer for adaptation and mitigation programmes under the UNFCCC-Kyoto Conference of Parties. However, reaching a strong common position requires the cooperation of the AU member states. In this context, African regional integration is an opportunity for the AU to foster such cooperation among member states. The Treaty Establishing the African Economic Community (the Abuja Treaty), the Constitutive Act of the AU and the Protocol on the Relations between the AU and Regional Economic Communities (RECs) prioritise regional economic integration and call for states' cooperation, but the call has not yet been heeded. To realise deep and viable African integration, there must be a well-structured institutional and legal framework that defines the relationship between the AU, the AEC and the RECs. African regional integration is also seen as an avenue whereby the AU can create its own regional climate-change regime. In this regard, the AU's and RECs' normative framework on climate change is examined in order to assess whether it adequately integrates climate change issues. This study finds that although Africa is most vulnerable to the consequences of climate change, the AU's and RECs' normative framework on climate change is weak and inadequate to address the problem. The Framework should integrate climate change issues in order to achieve sustainable development. The AU should also ensure that member states ratify the relevant treaties and protocols (the Maputo Nature Convention and the Protocol establishing the African Court of Justice and Human Rights) that have not yet been ratified in order that they may become operational. The Maputo Nature Convention puts sustainable development in the forefront of attention as a reaction to the potentially conflicting environmental and developmental challenges facing the continent (such as climate change), but it is not yet in force. This work finds that human rights law can strengthen the AU's role in addressing climate change through its normative framework. The human rights approach to climate change under the African Charter on Human and Peoples' Rights (the Banjul Charter) is a viable avenue because human rights law forms the basis for states' responsibility based on human rights obligations and principles. The extraterritorial application of the Banjul Charter presents an avenue for AU institutions such as the Human Rights Commission and the African Human Rights Court to curb the effects of climate change through a human rights lens. The future of the AU is presented within the context of a set of recommendations that identify strong African regional integration as an avenue through which the AU can foster the cooperation of member states to address the consequences of climate change in the AU's and RECs' normative frameworks. General recommendations are made on the need for the international climate change regime to pay more attention to issues of funding, capacity building and technology development and transfer on the basis of the vulnerability principle and in relation to the principles of equity and common but differentiated responsibilities and respective capabilities. Also, the AU needs to strengthen its legal and institutional structures to ensure deep African integration that is capable of addressing common challenges such as the consequences of climate change.
Keywords: African Charter on Human and Peoples Rights; African Economic Community (AEC); Climate Change; EAC Treaty; ECOWAS Treaty; Human rights; International climate change regime; Normative framework; Regional integration; SADC Treaty; State cooperation; The Constitutive Act of AU